The potential of weed control to improve seed production in selected tropical forage legumes - Kachelriess, S.; Tarawali, Shirley A. (New Zealand Grassland Association, 1993)
Trials have been conducted in the subhumid zone of Nigeria to assess the potential of different weed control methods to improve seed quantity and quality using three tropical forage legumes: Centrosema pascuorum cv. cavalcade, chamaecrista rotundifolia cv. Wynn and Stylosanthes hamata cv. Verano. Manual weeding was done at different times and intervals during the growing season and a range of herbicides was tested at different application rates and times. Manual weeding generally produced higher seed yields and purity if plots were weeded in the early and mid growing season. Intervals between weedings and the frequency of weeding was flexible and suitable for small scale seed production. Susceptibility of weeds and tolerance of legumes to various herbicides differed. Trifluralin has potential in Cavalcade, a combined application of bentazon and cyloxidim in Verano and imazethapyr in Wynn. Herbicide application is very time specific and needs to be done using appropriate equipment, it is therefore only recommended for specialised farmers.